2017
DOI: 10.1111/obr.12626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics on body weight, body mass index, fat mass and fat percentage in subjects with overweight or obesity: a systematic review and meta‐analysis of randomized controlled trials

Abstract: SummaryA systematic review and meta-analysis of randomized controlled trials was conducted to examine the effects of probiotic supplementation on body weight, body mass index (BMI), fat mass and fat percentage in subjects with overweight (BMI 25-29.9 kg m À2 ) or obesity (BMI ≥30 kg m À2). MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were searched for studies published between 1946 and September 2016. A meta-analysis, using a random effects model, was performed to calculate the weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(174 citation statements)
references
References 48 publications
10
140
1
2
Order By: Relevance
“…Regarding the morphology of the adipose tissue, absolute weight was determined and mean relative weight was calculated; represented data indicated nonsignificance between the different groups; and that was expected cause of kefir beverage feeding had no effects in increasing fat mass formed, also there were no histopathological changes between the normal animals and diabetic ones.The number of studies included in the metaanalyses of the effects of probiotics on body fat mass and the percentage was low, thus meaning that the latter results should be interpreted with caution.The agreements go with the overall of the seven studies reporting changes in fat mass showed a larger reduction in body fat mass and fat percentage in the intervention groups compared with the control groups, but the difference was non-significant because effect sizes were small (Borgeraas et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Regarding the morphology of the adipose tissue, absolute weight was determined and mean relative weight was calculated; represented data indicated nonsignificance between the different groups; and that was expected cause of kefir beverage feeding had no effects in increasing fat mass formed, also there were no histopathological changes between the normal animals and diabetic ones.The number of studies included in the metaanalyses of the effects of probiotics on body fat mass and the percentage was low, thus meaning that the latter results should be interpreted with caution.The agreements go with the overall of the seven studies reporting changes in fat mass showed a larger reduction in body fat mass and fat percentage in the intervention groups compared with the control groups, but the difference was non-significant because effect sizes were small (Borgeraas et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…et al, (2007) explained that the bodyweight of the diabetic rats which induced experimentally by streptozotocin decreased comparing with the normal rats. Yasamin et al, (2016) observed in their study that Kefir drink leads to a similar weight loss, compared with milk in overweight or obese premenopausal women.A total of 13 studies revealed the effects of probiotic supplementation consumption and found that the administration of probiotics was associated with a significantly larger reduction in BMI and weight loss (Borgeraas et al, 2018). Zemel et al, (2004) hypothesized that a dairy-rich diet containing kefir drink would lead to a greater weight loss, as kefir drink might have the antiobesity properties of dairy products and probiotics in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, administration of probiotics resulted in a significantly larger reduction in body weight expressed as BMI compared to placebo; however, the effect was small. In contrast, the effect of probiotics on fat mass was non-significant [54]. With obesity being the main driver of NAFLD, it is interesting to evaluate the effects of the induced gut flora modification in obese patients.…”
Section: Probiotics/prebioticsmentioning
confidence: 99%
“…Each treatment was performed in triplicates in order to calculate mean and standard deviation. The control randomised design (CRD) for the randomisation of eighteen experimental units (total six treatments with triplicates of each) was designed by using table of randomisation (Borgeraas et al ., ).…”
Section: Methodsmentioning
confidence: 97%